NON-ENZYMATIC BIOCHEMICAL RESPONSE OF OCIMUM SANCTUM TO NACL STRESS - Bajpai, Monika Shukla (Innovare Journal of Sciences, 2016)
Abstract Ocimum sanctum is a pharmaceutically important medicinal plant. In the present study the experimental plant was subjected to different concentrations (0, 20,40,60,80 Î¼M) of sodium chloride, a popular pollutant of saline stressed soils and non enzymatic antioxidant defense generated was studied in the leaves of Ocimum sanctum L. The non enzymatic parameters investigated include ascorbic acid, proline, glutathione and non protein thiol. As the concentration of NaCl was increased, except non protein thiol, all other three parameters displayed a decreasing trend as compared with control. Our results clearly indicate that non protein thiol is the key player among the non enzymatic parameters which protects the Ocimum sanctum against the deleterious effect of reactive oxygen species. Â Keywords: Ocimum sanctum, Salt Stress, Ascorbic acid, Glutathione, Proline, Non protein thiol.